Emergence of maqamah genre: a historical perspective (2010)
Art is influenced by and life itself is reflected in works of art. These sometimes reflect the experiences in social, education, spiritual and other aspect of life. The emergence of Maqamah art in the history of Arabic literature in the 4th Century after Hijrah pioneered by Badi’i-z-zaman al- Hamadhani (d.398 A.H.) has marked the great gestures and epoch by the scholars of note in their various literary art. Maqamah as an art denotes different meanings and values with fully rhymed prose with intervals of poetry in which rhetorical extravagance is conscious. And the imnterse of the scholars on this gerne has contributed immensely in promoting their literary skills, tastes and gestures. An attempt is being made in this paper to showcase the historical aspect of Maqamah genre as a new epoch in Arabic literature. Likewise, the position of Arabic literature in Abbasid age, and emergence of Maqamah writers will be highlighted for historical purpose.